An Intercenter Comparison of Dental Arch Relationships and Craniofacial Form Including a Center Using Nasoalveolar Molding. (July 2018) - Peanchitlertkajorn, Supakit; Mercado, Ana; Daskalogiannakis, John; Hathaway, Ronald; Russell, Kathleen; Semb, Gunvor; Shaw, William; Lamichane, Manish; Fessler, Jennifer; Long, Ross E.
Objective: To compare dental arch relationship and craniofacial morphology of patients with CUCLP in pre-adolescence from five cleft centers including a center using NAM. Design: Retrospective cohort study. Setting: Five cleft centers in North America. Patients: One hundred eighty-two subjects with repaired CUCLP from the five cleft centers participated in the craniofacial form study. One hundred forty-eight subjects from four of the five centers participated in the dental arch relationship study. Methods: Digital dental models were assessed using the GOSLON Yardstick. Eighteen cephalometric measurements were performed. Measurement means, by center, were compared. Analysis of variance and Tukey-Kramer analysis were used to compare GOSLON scores and cephalometric measurements. Results: The center that performed neither PSOT (including NAM) nor primary bone grafting exhibited the most favorable mean GOSLON score. The same center also showed the highest mean SNA, ANB, and ANS-N-Pg angles. However, the mean ANB and ANS-N-Pg angles were not significantly different from those of the center using NAM. No statistically significant differences were seen for mandibular prominence, vertical dimensions, or dental inclinations. The center with NAM also showed a significantly smaller nasoform angle than two of the four other centers. Conclusion: The centers that used NAM and other forms of PSOT did not have better dental arch relationships or craniofacial morphology compared with the centers that performed only primary lip repair. However, this study was not designed to investigate the cause-and-effect relationship between specific outcomes and particular features of those protocols.